Konflikty religijne jako podłoże zamiaru ludobójczego na przykładzie konfliktu bośniackiego - Spychalska, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the issue of religious conflicts as acause of genocide intent. The author based hers considerations on an analysis of the war in Bosnia 1992–1995. Though it was not a religious war, religion was an important instrument in this conflict. First, it became the primary factor in defining ethnic groups — enemies and allies. Second, religious symbols and religious rhetoric were used to foster nationalist ideology, gain public support for bloody war and provide justification for aggression and mass atrocities. In this way, religious differences used for achieving political goals became the reason for one of the most shocking genocides — the Srebrenica massacre.
Keywords: ludobójstwo; zamiar ludobójstwa; religia; konflikty religijne; Srebrenica